Dokumenter Animasi: Sebuah Kritik Wacana Visual - Adi, Anggar Erdhina (Capture : Jurnal Seni Media Rekam, 2011)
Animation documentary is a contemporary phenomen, it come together with reality and film naration, eventhough the value of reality  does not fixed. By psychoanalisis approach, this article try to explore the value of ideology as visual image representation about reality. Debating of visual image does not as reality representation, and it can be minimalized by understanding of visual metaphore which used by animation documentary filmmaker.Key words : film, documentary, animation, psychoanalysis, and ideology